Predictors of First Lifetime Onset of Major Depressive Disorder in Young Adulthood - Klein, Daniel N. (2012)
The first onset of major depressive disorder (MDD) most frequently occurs in young adulthood. However, few studies have examined predictors of first lifetime MDD during this high-risk period. The present study examined a broad range of demographic, clinical, and psychosocial variables as prospective predictors of first onset of MDD in a large community sample of young adults (N = 502) from the Oregon Adolescent Depression Project. Between ages 19-31, 35.3% of the sample had a first lifetime MDD episode. Female gender, familial loading of mood disorders, history of childhood sexual abuse, prior history of anxiety disorder, poor self-reported physical health, and subthreshold depressive symptoms significantly predicted MDD onset. In a multivariate model, female gender, familial loading of mood disorders, and subthreshold depression each contributed unique variance in predicting first lifetime MDD. This model had a moderate-to-large effect in predicting MDD onset. Gender did not moderate the other predictors, and the magnitude of the effects did not diminish over the course of the follow-up. These findings indicate that a number of risk factors significantly predict first lifetime MDD in young adulthood, and that simple multivariate risk models may be useful for identifying individuals at high risk for MDD.